Preparation method and application of tungsten oxide composite photo-anode

Through Fe, Ni doping and Pt-loaded tungsten oxide photoelectric anode materials, the problem of insufficient yield and selectivity in the catalytic water oxidation method of tungsten oxide is solved, efficient hydrogen peroxide production is achieved, and an economical and feasible cleaning is provided. Energy conversion method.

CN119243246APending Publication Date: 2025-01-03HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411482916.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the existing photoelectric catalytic technology, the yield and selectivity of the tungsten oxide photoanode is insufficient when preparing hydrogen peroxide (H2O2) by water oxidation, and there is a lack of effective cocatalyst to improve its efficiency.

Method used

The tungsten oxide (WO3) material co-doped with Fe and Ni elements and loaded with Pt nanocrystals on its surface, and vertically grown nanosheet morphology was prepared by hydrothermal method and photoreduction method to form Pt/FeNi/WO3 composite photoelectricity Anode material.

Benefits of technology

It significantly improves the yield and selectivity of hydrogen peroxide, provides an efficient photoelectric catalytic method that can be applied on a large scale at low cost and low energy consumption, effectively converting solar energy into clean energy, and alleviating energy shortages and environmental pollution problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243246A_ABST
    Figure CN119243246A_ABST
Patent Text Reader

Abstract

The invention discloses a tungsten oxide composite photo-anode material, the material is a composite material with Fe and Ni elements co-doped with WO3 and loaded with Pt nanocrystals, the material comprises a WO3 nanosheet vertically arranged on a substrate, Fe and Ni co-doped with the WO3 surface, and Pt nanocrystals loaded on the surface of the nanosheet, and the substrate is FTO conductive glass. The invention further discloses a preparation method of the tungsten oxide composite photo-anode material and application of the tungsten oxide composite photo-anode material in preparation of hydrogen peroxide through photoelectrocatalysis. The Pt / FeNi / WO3 composite photoanode material disclosed by the invention can be used as an efficient photoanode material, can be particularly used for preparing H2O2 by oxidizing water in a photoelectrochemical pool, can efficiently convert solar energy into clean energy, and effectively relieves the current situations of fossil fuel shortage, serious environmental pollution and the like at present.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectrocatalysis, and in particular relates to a preparation method of a tungsten oxide composite photoanode and an application thereof. Background Art

[0002] With the development and progress of industry and technology and the continuous growth of population, a large amount of urban sewage and industrial wastewater are discharged into natural water bodies without restraint. This behavior has caused serious water pollution problems and caused serious damage to the ecological environment. At the same time, the rapid consumption of fossil energy has brought about a serious energy crisis, and a large amount of pollutants will be emitted during the combustion of fossil energy, which has aggravated the pollution of the environment. The lack and shortage of energy has gradually become one of the key reasons restricting the development of human society. It can be seen that environmental pollution and energy crisis have become the main constraints on the sustainable development of human society. Therefore, the development of new, green and renewable clean energy is the focus of global environmental science and new energy fields. Among many new energy sources, solar energy is particularly concerned because of its easy availability, pollution-free, high utilization rate and high energy content. In addition, since the current scientific research on the utilization of solar energy is not thorough, this has led to a large amount of untapped usable energy in solar energy.

[0003] Photoelectrochemistry (PEC) is a catalytic process that converts light energy into chemical energy. It combines the principles of photocatalysis and electrocatalysis. In the PEC system, photosensitive materials (usually semiconductors) generate electron-hole pairs under light. These charge carriers migrate on the surface of the material or through an external circuit to participate in redox reactions, thereby achieving chemical transformation processes such as water decomposition, carbon dioxide reduction, and organic synthesis. In short, PEC technology uses light energy to excite semiconductor materials to generate electric current, which in turn drives chemical reactions to achieve energy conversion and material transformation. How to effectively and efficiently improve the working efficiency of photoelectrocatalytic water decomposition systems has become a major problem that has attracted much attention in the scientific field. Once there is a breakthrough in this field, it will have an important impact on global energy and environmental issues.

[0004] Hydrogen peroxide (H 2 O 2 ) is a liquid at room temperature and pressure, so without using a high-pressure water tank, its energy density per unit volume is very high. 2 O 2 It can be used as a fuel cell, which can act as both the negative electrode oxidant and the anode reductant, providing a theoretical output voltage of 1.09V. At the same time, after energy release, its products are only water and oxygen. At present, the anthraquinone method and the direct hydrogen-oxygen synthesis method are commonly used in industry and laboratories to prepare H 2 O 2Different from these two methods, photoelectrocatalytic water oxidation method can produce H 2 O 2 , is a more economical and accessible preparation method. This reaction process only uses water as a reactant, and through the direct action of light and an external electric field, water can be directly oxidized into H 2 O 2 However, the photoelectrocatalytic water oxidation method for the preparation of H 2 O 2 There are few studies on this topic.

[0005] Tungsten trioxide (WO 3 ) is a typical wide bandgap semiconductor, which is often used as a photoanode material in photoelectrochemical reactions due to its low toxicity, excellent electron transport performance and certain visible light response (Eg ~ 2.7eV). 3 As a photoanode, it still has some disadvantages. Because of its large bandgap, it cannot fully absorb and utilize visible light, and its photogenerated carrier recombination rate is high. Although WO 3 The valence band (VB) position of WO is suitable for oxygen production, but its conduction band (CB) position is more positive than the reduction potential of water. 3 A series of research improvements have been carried out to improve these shortcomings, such as doping, modifying co-catalysts, combining with other semiconductors to build heterojunctions, and introducing oxygen vacancies to improve WO 3 In 1976, Honda first used WO 3 As a photoanode for photoelectrocatalytic water decomposition [G. Hodes, D. Cahen, J. Manassen, Nature, 1976, 260: 312-313], it has attracted widespread attention from researchers. However, it has not been possible to increase the target product H from the perspective of co-catalyst. 2 O 2 yield and improve its selectivity.

[0006] Therefore, developing a material and preparation method that is low-cost, low-energy, has a simple synthesis process, and can significantly improve the photoelectrochemical performance of tungsten oxide photoanode has important scientific significance and application value. Summary of the invention

[0007] In view of the deficiencies of the prior art and actual needs, the present invention provides a semiconductor anode material for photoelectrocatalytic preparation of hydrogen peroxide and a preparation method thereof, that is, a semiconductor anode material that can promote the photoelectrocatalytic water oxidation method to prepare H 2 O 2 The process is highly efficient Pt / FeNi / WO 3 Composite photoanode material and preparation method thereof.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] In the first aspect, the present invention provides a tungsten oxide composite photoanode material, characterized in that the material is WO co-doped with Fe and Ni elements. 3 A composite material loaded with Pt nanocrystals, comprising WO arranged vertically on a substrate 3 Nanosheets, co-doped WO 3 The substrate is FTO conductive glass.

[0010] In one or more embodiments, the WO 3 The thickness of the nanosheet is 60-120 nm, preferably 70-120 nm; the WO 3 The length and width of the nanosheet are both 300-700 nm, preferably 500-700 nm; the diameter of the Pt nanocrystal is 5-60 nm, preferably 20-50 nm.

[0011] In one or more embodiments, WO is present on each square centimeter of the substrate. 3 The mass of the nanosheet is 2-8 mg, and the mass of the Pt nanocrystal is WO 3 0.12-7.5% of the mass of the nanosheet, preferably 0.5-7.5%; the mass of the Fe element is WO 3 The mass of the Ni element is 0.5-0.7% of the mass of the nanosheet; the mass of the Ni element is WO 3 0.5-0.7% of the mass of the nanosheets.

[0012] In a second aspect, the present invention provides a method for preparing the tungsten oxide composite photoanode material, the preparation method comprising the following steps:

[0013] S1. Place the substrate on WO 3 The nanosheets are hydrothermally grown in a precursor solution at a temperature of 140-200°C for 3-8 hours. The sample is then washed and dried and calcined at 400-600°C for 1-3 hours to obtain vertically grown WO 3 The substrate of the nanosheet;

[0014] S2, the vertically grown WO prepared in step S1 3 The Pt precursor solution is evenly dispersed on the substrate of the nanosheets to make the WO 3 The surface of the nanosheet is loaded with Pt nanocrystals, which are then dried at 50-70°C to obtain Pt / WO 3 Composite materials;

[0015] S3, Pt / WO prepared in step S2 3The Fe and Ni element precursor solutions are evenly dispersed on the composite material to make Pt / WO 3 The composite material is loaded with Fe and Ni elements on its surface, and then dried at 30-80°C to obtain the tungsten oxide composite photoanode material Pt / FeNi / WO 3 .

[0016] In one or more embodiments, the substrate in step S1 needs to be ultrasonically cleaned in acetone, ethanol and deionized water for 10-50 minutes respectively before the hydrothermal process.

[0017] In one or more embodiments, the WO in step S1 3 The nanosheet precursor solution was prepared according to the following steps:

[0018] (1) Deionized water, concentrated hydrochloric acid and ammonium tungstate were stirred in a volume ratio of 20:1:1 to fully mix and obtain WO 3 Nanosheet precursor a solution, concentrated hydrochloric acid is a 20-38% by mass hydrogen chloride aqueous solution;

[0019] (2)In WO 3 Add 30% hydrogen peroxide solution to the nanosheet precursor a solution and stir thoroughly to mix well to obtain WO 3 A nanosheet precursor b solution, wherein the volume ratio of the aqueous hydrogen peroxide solution to the deionized water in step (1) is (0.8-1):45, preferably (0.85-0.9):45;

[0020] (3)In WO 3 Ammonium oxalate was added to the nanosheet precursor b solution and stirred thoroughly to obtain the WO 3 The volume ratio of the nanosheet precursor solution, ammonium oxalate and the deionized water in step (1) is (1-2):100, preferably (1-1.5):100.

[0021] In one or more embodiments, the uniform dispersion of the Pt precursor solution in step S2 is performed according to the following steps:

[0022] (1) mixing anhydrous methanol and a hexachloroplatinic acid aqueous solution uniformly to obtain a Pt precursor solution, wherein the volume ratio of anhydrous methanol to the hexachloroplatinic acid aqueous solution is (600-800):(1-10), and the concentration of platinum chloride in the hexachloroplatinic acid solution is 1-50 mg / ml;

[0023] (2) The Pt precursor solution obtained in step (1) is placed under a xenon lamp and illuminated for 1-3 hours at an intensity of one sun.

[0024] In one or more embodiments, the uniformly dispersed Fe and Ni element precursor solution in step S3 is prepared according to the following steps:

[0025] (1) mixing anhydrous methanol, ferric chloride and nickel chloride uniformly to obtain Fe and Ni element precursor solutions, wherein the volume ratio of anhydrous methanol, ferric chloride and nickel chloride is (600-800):(1-5):(1-10);

[0026] (2) The Fe and Ni element precursor solutions obtained in step (1) are placed under a xenon lamp and illuminated for 1-2 hours at an intensity of one sun.

[0027] In one or more embodiments, the substrate needs to be cleaned before the drying steps in steps S2 and S3.

[0028] In a third aspect, the present invention also includes the use of the tungsten oxide composite photoanode material described in any one of the above items or the tungsten oxide composite photoanode material obtained by any one of the preparation methods described in the photoelectrocatalytic preparation of hydrogen peroxide.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) Pt / FeNi / WO of the present invention 3 The composite photoanode material has a simple and easy preparation method, does not require large-scale instruments and equipment, and is economically feasible; its preparation process is highly controllable, the reaction conditions are milder, the reaction time is shorter, and it has certain industrial value.

[0031] (2) The tungsten oxide composite photoanode material of the present invention has a large specific surface area, providing a direct and smooth transmission path for photogenerated electrons and holes, and can effectively promote the transfer of electrons to the interface of the material (solid-solid or liquid-solid). The loaded Pt nanocrystals have the effect of promoting the water oxidation reaction to the two-electron path 2H 2 O→H 2 O 2 The conversion effect is better than that of simple WO 3 Nanofilm, Pt / FeNi / WO 3 Composite photoanode materials in the target product H 2 O 2 The yield and selectivity were significantly improved.

[0032] (3) Pt / FeNi / WO of the present invention 3 The composite photoanode material can be used as a highly efficient photoanode material, specifically for photoelectrochemical cell oxidation of water to produce H 2 O 2 , which can efficiently convert solar energy into clean energy, effectively alleviating the current situation of fossil fuel shortage and serious environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a scanning electron microscope (SEM) image of the tungsten oxide composite photoanode material prepared in Example 1;

[0034] Figure 2 is the X-ray diffraction (XRD) spectrum of the tungsten oxide composite photoanode material prepared in Example 1;

[0035] Figure 3 It is a comparison chart of the hydrogen peroxide production of the tungsten oxide composite photoanode material prepared in Example 1 and the control material under light conditions. DETAILED DESCRIPTION

[0036] Photoelectrocatalytic water oxidation to produce H 2 O 2 , is an economical and readily available preparation method. This reaction process only uses water as a reactant, and through the direct action of light and an external electric field, water can be directly oxidized into H 2 O 2 Unfortunately, the photoelectrocatalytic water oxidation method for the preparation of H 2 O 2 There are few studies on this topic.

[0037] Fuku and Sayama found in 2016 that when KHCO 3 When used as an electrolyte, it can significantly increase the target product H 2 O 2 The yield is due to the generation of HCO 3 - Can be used as H 2 O to H 2 O 2 oxidant, thereby promoting the reaction. Norskov and Zheng Xiaolin also proved from the perspective of experiments and theoretical calculations in 2017 that TiO 2 and WO 3 Materials such as these can be used for photoelectrocatalytic water oxidation to produce H 2 O 2 However, it has not been possible to increase the target product H from the perspective of co-catalyst. 2 O 2 yield and improve its selectivity.

[0038] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a tungsten oxide composite photoanode material and a preparation method thereof, that is, a tungsten oxide composite photoanode material that can promote the photoelectrocatalytic water oxidation method to prepare H 2 O 2The high-efficiency tungsten oxide composite photoanode material and its preparation method for this process. In this technical solution, the one-dimensional nanosheet morphology effectively increases the specific surface area of ​​the thin film material, fully absorbs light energy, and increases the photocurrent. At the same time, the Fe and Ni elements and Pt nanocrystals loaded on the nanosheets act as co-catalysts, which can effectively promote the water oxidation reaction to the two-electron path 2H 2 O→H 2 O 2 conversion, increasing the target product H 2 O 2 It has high yield and selectivity, good chemical stability, and its preparation method is simple, which can be used in a low-cost and large-scale manner.

[0039] Specifically, the composite photoanode material of the present invention is WO co-doped with Fe and Ni elements. 3 A composite material loaded with Pt nanocrystals, comprising WO arranged vertically on a substrate 3 Nanosheets, co-doped WO 3 The substrate is FTO conductive glass.

[0040] It should be understood that the material described in the present invention only defines its basic composition and the parameters for defining its specific composition, such as the area size of the substrate, the WO 3 The mass, thickness, length and width of the nanosheets, the size and mass of the Pt nanocrystals, the mass of the Fe and Ni elements, etc., can be appropriately adjusted according to actual needs during the actual preparation process. 3 In the preparation process of the composite material, the relevant parameters can be increased, and vice versa. In addition, in the preparation of the material of the present invention, the initial feed and process parameters need to be calculated according to the mass conservation and feed ratio.

[0041] In order to facilitate the description of the composite material of the present invention, the WO 3 The thickness of the nanosheet can be 60-120 nm, preferably 70-110 nm; the WO 3 The length and width of the nanosheet can be 300-700nm, preferably 500-700nm; the diameter of the Pt nanocrystal can be 5-60nm, preferably 20-50nm; the substrate can be 1*1cm 2 FTO conductive glass.

[0042] In order to facilitate the description of the composite material of the present invention, WO 3 The mass of the nanosheet is 2-8 mg, and the mass of the Pt nanocrystal is WO3 0.12-7.5% of the mass of the nanosheet, preferably 0.5-7.5%; the mass of the Fe element is WO 3 The mass of the Ni element is 0.5-0.7% of the mass of the nanosheet; the mass of the Ni element is WO 3 0.5-0.7% of the mass of the nanosheets.

[0043] In addition, the present invention also includes a method for preparing the tungsten oxide composite photoanode material, which comprises the following steps:

[0044] S1. Place the substrate on WO 3 The nanosheets are hydrothermally grown in a precursor solution at a temperature of 140-200°C for 3-8 hours. The sample is then washed and dried and calcined at 400-600°C for 1-3 hours to obtain vertically grown WO 3 The substrate of the nanosheet;

[0045] S2, the vertically grown WO prepared in step S1 3 The Pt precursor solution is evenly dispersed on the substrate of the nanosheets to make the WO 3 The surface of the nanosheet is loaded with Pt nanocrystals, which are then dried at 50-70°C to obtain Pt / WO 3 Composite materials;

[0046] S3, Pt / WO prepared in step S2 3 The Fe and Ni element precursor solutions are evenly dispersed on the composite material to make Pt / WO 3 The composite material is loaded with Fe and Ni elements on its surface, and then dried at 30-80°C to obtain the tungsten oxide composite photoanode material Pt / FeNi / WO 3 .

[0047] It should be understood that the terms and expressions involved in the preparation method described in the present invention are common knowledge in the art. The substrate described in step S1 needs to be cleaned before the hydrothermal process. Preferably, the substrate is ultrasonically cleaned in acetone, ethanol and deionized water for 10-50 minutes respectively before the hydrothermal process.

[0048] It should be understood that in step S1 of the preparation method of the present invention, the WO 3 The nanosheet precursor solution can be prepared or configured according to any method in the art. Preferably, it can be prepared according to the following steps:

[0049] (1) Deionized water, concentrated hydrochloric acid and ammonium tungstate were stirred in a volume ratio of 20:1:1 to fully mix and obtain WO 3Nanosheet precursor a solution, concentrated hydrochloric acid is a 20-38% by mass hydrogen chloride aqueous solution;

[0050] (2)In WO 3 Add 30% hydrogen peroxide solution to the nanosheet precursor a solution and stir thoroughly to mix well to obtain WO 3 A nanosheet precursor b solution, wherein the volume ratio of the aqueous hydrogen peroxide solution to the deionized water in step (1) is (0.8-1):45, preferably (0.85-0.9):45;

[0051] (3)In WO 3 Ammonium oxalate was added to the nanosheet precursor b solution and stirred thoroughly to obtain the WO 3 The volume ratio of the nanosheet precursor solution, ammonium oxalate and the deionized water in step (1) is (1-2):100, preferably (1-1.5):100.

[0052] It should be understood that in step S2 of the preparation method of the present invention, the uniformly dispersed Pt precursor solution can be prepared according to any method in the art. Preferably, it can be prepared according to the following steps:

[0053] (1) mixing anhydrous methanol and a hexachloroplatinic acid aqueous solution uniformly to obtain a Pt precursor solution, wherein the volume ratio of anhydrous methanol to the hexachloroplatinic acid aqueous solution is (600-800):(1-10), and the concentration of platinum chloride in the hexachloroplatinic acid solution is 1-50 mg / ml;

[0054] (2) The Pt precursor solution obtained in step (1) is placed under a xenon lamp and illuminated for 1-3 hours at an intensity of one sun.

[0055] Specifically, it is possible to grow WO 3 The Pt precursor solution prepared in the above step (1) is dripped, sprayed or coated on the substrate of the nanosheet. Since there are gaps between the tungsten trioxide nanosheets, the hexachloroplatinic acid aqueous solution will be between the tungsten trioxide nanosheets and on the top of the tungsten trioxide nanosheets, so that the Pt nanocrystals are dispersed between the tungsten trioxide nanosheets and on the top of the tungsten trioxide nanosheets (i.e., the surface of the tungsten trioxide nanosheets).

[0056] It should be understood that in step S2 of the preparation method of the present invention, the uniformly dispersed Fe and Ni element precursor solution can be prepared according to any method in the art. Preferably, the following steps can be followed:

[0057] (1) mixing anhydrous methanol, ferric chloride and nickel chloride uniformly to obtain Fe and Ni element precursor solutions, wherein the volume ratio of anhydrous methanol, ferric chloride and nickel chloride is (600-800):(1-5):(1-10);

[0058] (2) The Fe and Ni element precursor solutions obtained in step (1) are placed under a xenon lamp and illuminated for 1-2 hours at an intensity of one sun.

[0059] Specifically, it is possible to grow WO 3 The substrate of the nanosheet is dripped, sprayed or coated with the solution of uniformly dispersed iron salt and nickel salt prepared in the above step (1). Since there are gaps between the tungsten trioxide nanosheets, the aqueous solution will be between the tungsten trioxide nanosheets and on the top of the tungsten trioxide nanosheets, so that the Fe and Ni elements can be evenly distributed on the tungsten trioxide substrate (i.e., the surface of the tungsten trioxide nanosheets).

[0060] It should be understood that in the preparation method, in order to improve the final product composite photoanode material Pt / FeNi / WO 3 In order to improve the quality of the substrate, the substrate needs to be cleaned before the drying steps in steps S2 and S3.

[0061] It is well known to those skilled in the art that the photoreduction method has obvious advantages over the electrochemical deposition method. Specifically, the principle of the electrochemical deposition method is based on the application of current in the electrolyte solution to cause an oxidation reaction at the anode and a reduction reaction at the cathode, so that the metal ions obtain electrons on the cathode surface and are deposited into a solid state; while the photoreduction method uses light energy to generate electrons through the absorption of light energy by photosensitizers, and these electrons reduce metal ions to metals. The whole process does not involve the application of current, but relies on light energy to drive the reduction reaction.

[0062] The tungsten trioxide substrate proposed in the present invention is prepared by a simple hydrothermal method. The prepared precursor solution is poured into the inner lining of the reactor for hydrothermal reaction. After the reaction, the substrate is dried and annealed to obtain the substrate. Different from the electrochemical deposition method in the prior art, a simpler hydrothermal method is used to deposit Pt, Fe, and Ni, and finally a photoanode material is obtained, and the preparation method is simpler.

[0063] Compared with the reported materials, the material of the present invention combines three elements and effectively improves the photocatalytic activity of tungsten oxide. The present invention has positive significance for the issue of energy utilization and provides a new direction for environmentally friendly green water treatment technology.

[0064] Example

[0065] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0066] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.

[0067] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.

[0068] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0069] The examples involve the addition amounts, contents and concentrations of various substances, wherein the percentages described therein, unless otherwise specified, are all by mass percentages.

[0070] Example 1: A tungsten oxide composite photoanode material Pt / FeNi / WO 3 Preparation

[0071] #1-WO 3 Nanosheet precursor solution:

[0072] (1) Deionized water, concentrated hydrochloric acid and ammonium tungstate were stirred in a volume ratio of 20:1:1 to fully mix and obtain WO 3 A nanosheet precursor a solution, wherein the concentrated hydrochloric acid is a 35% by mass aqueous solution of hydrogen chloride;

[0073] (2)In WO 3 Add 30% hydrogen peroxide solution to the nanosheet precursor a solution and stir thoroughly to mix well to obtain WO 3 A nanosheet precursor b solution, wherein the volume ratio of the aqueous hydrogen peroxide solution to the deionized water in step (1) is 0.9:45;

[0074] (3)In WO 3Ammonium oxalate was added to the nanosheet precursor b solution and stirred thoroughly to obtain the WO 3 The volume ratio of the nanosheet precursor solution, ammonium oxalate and the deionized water in step (1) is 1.5:100.

[0075] #2-Pt precursor solution preparation:

[0076] The anhydrous methanol and the hexachloroplatinic acid aqueous solution are evenly mixed to obtain a Pt precursor solution, wherein the volume ratio of the anhydrous methanol to the hexachloroplatinic acid aqueous solution is 700:3, and the concentration of platinum chloride in the hexachloroplatinic acid solution is 35 mg / ml.

[0077] #3-Preparation of Fe and Ni precursor solutions:

[0078] Anhydrous methanol, ferric chloride and nickel chloride are uniformly mixed to obtain Fe and Ni element precursor solutions, wherein the volume ratio of anhydrous methanol, ferric chloride and nickel chloride is 700:2:5.

[0079] #4-WO 3 Hydrothermal growth of nanosheets:

[0080] The substrate FTO conductive glass was ultrasonically cleaned in acetone, ethanol and deionized water for 30 min respectively, and then the substrate was placed on the WO prepared in step #1. 3 The nanosheets were hydrothermally grown in the precursor solution (the conductive surface of the FTO conductive glass was facing downward), the hydrothermal temperature was 170°C, the hydrothermal time was 5 hours, and then the sample was washed and dried and calcined at 480°C for 2 hours to obtain vertically grown WO 3 Nanosheet substrate.

[0081] #5-Pt / WO 3 Preparation of composite materials:

[0082] The vertically grown WO prepared in step #4 above 3 The Pt precursor solution prepared in step #2 is evenly dispersed on the substrate of the nanosheet, and the solution is placed under a xenon lamp and illuminated for 2 hours at an intensity of one sun to allow WO 3 The surface of the nanosheets is loaded with Pt nanocrystals, which are then dried at 60°C to obtain Pt / WO 3 Composite materials.

[0083] #6-Pt / FeNi / WO 3 Preparation of composite photoanode materials:

[0084] Pt / WO prepared in step #5 3The Fe and Ni element precursor solutions prepared in step #3 are uniformly dispersed on the composite material, and the solution is placed under a xenon lamp and illuminated for 1.5 hours at a sunlight intensity to allow the Pt / WO 3 The composite material is loaded with Fe and Ni elements on its surface, and then dried at 60°C to obtain the tungsten oxide composite photoanode material Pt / FeNi / WO 3 .

[0085] The tungsten oxide composite photoanode material has a WO 3 The mass of the nanosheet is 6 mg, and the mass of the Pt nanocrystal is WO 3 The mass of the Fe element is 0.5% of the mass of the nanosheet; the mass of the Fe element is WO 3 The mass of the Ni element is 0.54% of the mass of the nanosheet; the mass of the Ni element is WO 3 0.6% of the mass of the nanosheets.

[0086] Example 2: A tungsten oxide composite photoanode material Pt / FeNi / WO 3 Preparation

[0087] #1-WO 3 Nanosheet precursor solution:

[0088] (1) Deionized water, concentrated hydrochloric acid and ammonium tungstate were stirred in a volume ratio of 20:1:1 to fully mix and obtain WO 3 Nanosheet precursor a solution, concentrated hydrochloric acid is a 38% by mass aqueous solution of hydrogen chloride;

[0089] (2)In WO 3 Add 30% hydrogen peroxide solution to the nanosheet precursor a solution and stir thoroughly to mix well to obtain WO 3 A nanosheet precursor b solution, wherein the volume ratio of the aqueous hydrogen peroxide solution to the deionized water in step (1) is 0.8:45;

[0090] (3)In WO 3 Ammonium oxalate was added to the nanosheet precursor b solution and stirred thoroughly to obtain the WO 3 The volume ratio of the nanosheet precursor solution, ammonium oxalate and the deionized water in step (1) is 1:100.

[0091] #2-Pt precursor solution preparation:

[0092] The anhydrous methanol and the hexachloroplatinic acid aqueous solution are evenly mixed to obtain a Pt precursor solution, wherein the volume ratio of the anhydrous methanol to the hexachloroplatinic acid aqueous solution is 600:10, and the concentration of platinum chloride in the hexachloroplatinic acid solution is 1 mg / ml.

[0093] #3-Preparation of Fe and Ni precursor solutions:

[0094] Anhydrous methanol, ferric chloride and nickel chloride are uniformly mixed to obtain Fe and Ni element precursor solutions, wherein the volume ratio of anhydrous methanol, ferric chloride and nickel chloride is 600:1:1.

[0095] #4-WO 3 Hydrothermal growth of nanosheets:

[0096] The substrate FTO conductive glass was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min respectively, and then the substrate was placed on the WO prepared in step #1. 3 The nanosheets were hydrothermally grown in the precursor solution (the conductive surface of the FTO conductive glass was facing downward), the hydrothermal temperature was 140°C, the hydrothermal time was 8 hours, and then the sample was washed and dried and calcined at 400°C for 3 hours to obtain vertically grown WO 3 Nanosheet substrate.

[0097] #5-Pt / WO 3 Preparation of composite materials:

[0098] The vertically grown WO prepared in step #4 above 3 The Pt precursor solution prepared in step #2 was evenly dispersed on the substrate of the nanosheet, and the solution was placed under a xenon lamp and illuminated for 1 hour at an intensity of one sun to allow WO 3 The surface of the nanosheets is loaded with Pt nanocrystals, which are then dried at 50°C to obtain Pt / WO 3 Composite materials.

[0099] #6-Pt / FeNi / WO 3 Preparation of composite photoanode materials:

[0100] Pt / WO prepared in step #5 3 The Fe and Ni element precursor solutions prepared in step #3 are uniformly dispersed on the composite material, and the solution is placed under a xenon lamp and illuminated for 2 hours at a sunlight intensity to make Pt / WO 3 The composite material is loaded with Fe and Ni elements on its surface, and then dried at 80°C to obtain the tungsten oxide composite photoanode material Pt / FeNi / WO 3 .

[0101] The tungsten oxide composite photoanode material has a WO 3 The mass of the nanosheet is 2 mg, and the mass of the Pt nanocrystal is WO 3 The mass of the Fe element is 7.5% of the mass of the nanosheet; the mass of the Fe element is WO 3The mass of the Ni element is 0.5% of the mass of the nanosheet; the mass of the Ni element is WO 3 0.7% of the mass of the nanosheets.

[0102] Example 3: A tungsten oxide composite photoanode material Pt / FeNi / WO 3 Preparation

[0103] #1-WO 3 Nanosheet precursor solution:

[0104] (1) Deionized water, concentrated hydrochloric acid and ammonium tungstate were stirred in a volume ratio of 20:1:1 to fully mix and obtain WO 3 Nanosheet precursor a solution, concentrated hydrochloric acid is a 20% by mass aqueous solution of hydrogen chloride;

[0105] (2)In WO 3 Add 30% hydrogen peroxide solution to the nanosheet precursor a solution and stir thoroughly to mix well to obtain WO 3 A nanosheet precursor b solution, wherein the volume ratio of the hydrogen peroxide solution to the deionized water in step (1) is 1:45;

[0106] (3)In WO 3 Ammonium oxalate was added to the nanosheet precursor b solution and stirred thoroughly to obtain the WO 3 The volume ratio of the nanosheet precursor solution, ammonium oxalate and the deionized water in step (1) is 2:100.

[0107] #2-Pt precursor solution preparation:

[0108] Anhydrous methanol and hexachloroplatinic acid aqueous solution are evenly mixed to obtain a Pt precursor solution, wherein the volume ratio of anhydrous methanol to hexachloroplatinic acid aqueous solution is 800:1, and the concentration of platinum chloride in the hexachloroplatinic acid solution is 50 mg / ml.

[0109] #3-Preparation of Fe and Ni precursor solutions:

[0110] Anhydrous methanol, ferric chloride and nickel chloride are uniformly mixed to obtain Fe and Ni element precursor solutions, wherein the volume ratio of anhydrous methanol, ferric chloride and nickel chloride is 800:5:10.

[0111] #4-WO 3 Hydrothermal growth of nanosheets:

[0112] The substrate FTO conductive glass was ultrasonically cleaned in acetone, ethanol and deionized water for 50 min respectively, and then the substrate was placed on the WO prepared in step #1. 3The nanosheets were hydrothermally grown in the precursor solution (the conductive surface of the FTO conductive glass was facing downward), the hydrothermal temperature was 200°C, the hydrothermal time was 3 hours, and then the sample was washed and dried and calcined at 600°C for 1 hour to obtain vertically grown WO 3 Nanosheet substrate.

[0113] #5-Pt / WO 3 Preparation of composite materials:

[0114] The vertically grown WO prepared in step #4 above 3 The Pt precursor solution prepared in step #2 was evenly dispersed on the substrate of the nanosheets, and the solution was placed under a xenon lamp at a sunlight intensity for 3 hours to allow WO 3 The surface of the nanosheets is loaded with Pt nanocrystals, which are then dried at 70°C to obtain Pt / WO 3 Composite materials.

[0115] #6-Pt / FeNi / WO 3 Preparation of composite photoanode materials:

[0116] Pt / WO prepared in step #5 3 The Fe and Ni element precursor solutions prepared in step #3 are uniformly dispersed on the composite material, and the solution is placed under a xenon lamp and illuminated for 1 hour at a sunlight intensity to make Pt / WO 3 The composite material is loaded with Fe and Ni elements on its surface, and then dried at 30°C to obtain the tungsten oxide composite photoanode material Pt / FeNi / WO 3 .

[0117] The tungsten oxide composite photoanode material has a WO 3 The mass of the nanosheet is 8 mg, and the mass of the Pt nanocrystal is WO 3 The mass of the Fe element is 0.12% of the mass of the nanosheet; the mass of the Fe element is WO 3 The mass of the Ni element is 0.7% of the mass of the nanosheet; the mass of the Ni element is WO 3 0.5% of the mass of the nanosheets.

[0118] Comparative Example 1: A tungsten oxide composite photoanode material Pt / WO 3 Preparation

[0119] #1-WO 3 Nanosheet precursor solution:

[0120] (1) Deionized water, concentrated hydrochloric acid and ammonium tungstate were stirred in a volume ratio of 20:1:1 to fully mix and obtain WO 3Nanosheet precursor a solution, concentrated hydrochloric acid is a 35% by mass aqueous solution of hydrogen chloride;

[0121] (2)In WO 3 Add 30% hydrogen peroxide solution to the nanosheet precursor a solution and stir thoroughly to mix well to obtain WO 3 A nanosheet precursor b solution, wherein the volume ratio of the aqueous hydrogen peroxide solution to the deionized water in step (1) is 0.9:45;

[0122] (3)In WO 3 Ammonium oxalate was added to the nanosheet precursor b solution and stirred thoroughly to obtain the WO 3 The volume ratio of the nanosheet precursor solution, ammonium oxalate and the deionized water in step (1) is 1.5:100.

[0123] #2-Pt precursor solution preparation:

[0124] The anhydrous methanol and the hexachloroplatinic acid aqueous solution are evenly mixed to obtain a Pt precursor solution, wherein the volume ratio of the anhydrous methanol to the hexachloroplatinic acid aqueous solution is 700:3, and the concentration of platinum chloride in the hexachloroplatinic acid solution is 35 mg / ml.

[0125] #3-WO 3 Hydrothermal growth of nanosheets:

[0126] The substrate FTO conductive glass was ultrasonically cleaned in acetone, ethanol and deionized water for 30 min respectively, and then the substrate was placed on the WO prepared in step #1. 3 The nanosheets were hydrothermally grown in the precursor solution (the conductive surface of the FTO conductive glass was facing downward), the hydrothermal temperature was 170°C, the hydrothermal time was 5 hours, and then the sample was washed and dried and calcined at 480°C for 2 hours to obtain vertically grown WO 3 Nanosheet substrate.

[0127] #4-Pt / WO 3 Preparation of composite materials:

[0128] The vertically grown WO prepared in step #3 above 3 The Pt precursor solution prepared in step #2 is evenly dispersed on the substrate of the nanosheet, and the solution is placed under a xenon lamp and illuminated for 2 hours at an intensity of one sun to allow WO 3 The surface of the nanosheets is loaded with Pt nanocrystals, which are then dried at 60°C to obtain Pt / WO 3 Composite materials.

[0129] The composite material has WO per square centimeter of substrate 3 The mass of the nanosheet is 6 mg, and the mass of the Pt nanocrystal is WO3 0.5% of the mass of the nanosheets.

[0130] Test example 1: Electron microscope test of tungsten oxide composite photoanode material

[0131] The tungsten oxide composite photoanode material prepared by the method described in Example 1 was detected using a scanning electron microscope. Figure 1 This is an electron microscope image of tungsten oxide co-doped with Fe and Ni elements and loaded with Pt nanocrystalline material. The nanoparticle size is 5-50nm. Figure 1 The results show that the material prepared by the above embodiment is a nanosheet structure grown vertically on the FTO surface with uniform morphology, and is very suitable as a photoanode material.

[0132] Detection Example 2: X-ray Detection of Tungsten Oxide Composite Photoanode Materials

[0133] The tungsten oxide composite photoanode material prepared by the method described in Example 1 was tested by X-ray diffraction (XRD). Figure 2 The results show that the sample prepared by the above example has multiple obvious diffraction peaks, indicating that the photoanode material prepared in Example 1 is a polycrystalline structure with good crystallinity. Test Example 3: Pt / FeNi / WO 3 Composite photoanode materials for photoelectrochemical cells to produce hydrogen peroxide via photoelectrocatalytic water oxidation

[0134] The Pt / FeNi / WO prepared in Example 1-3 3 Composite photoanode material, Pt / WO prepared in Comparative Example 1 3 Composites and WO 3 The material was used as the working electrode, the platinum electrode was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode to assemble a photoelectrochemical cell to study the photoelectric properties and photoelectrocatalytic water oxidation to prepare H 2 O 2 Performance test. The electrolyte is 0.2moL / L Na 2 SO 4 Aqueous solution (pH = 7), the illumination area of ​​the working electrode is 4 cm 2 A 300W xenon lamp was used with an AM 1.5G filter to obtain simulated sunlight. The light intensity at the working electrode of the photoelectrochemical cell was tested by a radiometer and was 100mW / cm 2 The applied voltage was 1.23V vs. RHE, and the test was conducted for 3 hours under AM 1.5G (simulated sunlight). The hydrogen peroxide production can be calculated by the DPD method.

[0135] The specific method of detecting hydrogen peroxide by DPD is as follows: first, the sample solution to be tested is mixed with DPD solution and sulfuric acid solution, and after sufficient shaking, it is allowed to stand for a certain period of time to allow DPD and hydrogen peroxide to react with color under acidic conditions; then, the absorbance of the mixed solution is measured at a wavelength of 510nm using a spectrophotometer; finally, the concentration of hydrogen peroxide in the sample solution is determined based on a pre-prepared hydrogen peroxide standard curve.

[0136] After 3 hours of reaction, the results of hydrogen peroxide production are shown in the following table. The results show that the amount of hydrogen peroxide produced by the tungsten oxide composite photoanode material prepared in Examples 1-3 of the present invention as a working electrode is significantly higher than that of the control.

[0137]

[0138]

[0139] In addition, if Figure 3 As shown, the Pt / FeNi / WO prepared in Example 1 3、 Pt / WO prepared in Comparative Example 1 3 and WO 3 From the comparison diagrams of hydrogen peroxide production of the working electrodes under light conditions, it can be intuitively seen that the tungsten oxide composite photoanode material of the present invention has a significantly higher hydrogen peroxide production than other materials.

[0140] The above is only an implementation method of the present invention. It should be pointed out that, for ordinary technicians in this field, changes can be made without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention.

Claims

1. A tungsten oxide composite photoanode material, characterized in that: The material is a composite material of WO3 co-doped with Fe and Ni elements and loaded with Pt nanocrystals, comprising WO3 nanosheets vertically arranged on a substrate, Fe and Ni co-doped on the surface of WO3, and Pt nanocrystals loaded on the surface of the nanosheets, and the substrate is FTO conductive glass.

2. The tungsten oxide composite photoanode material according to claim 1, characterized in that: The thickness of the WO3 nanosheet is 60-120nm, preferably 70-120nm; the length and width of the WO3 nanosheet are both 300-700nm, preferably 500-700nm; the diameter of the Pt nanocrystal is 5-60nm, preferably 20-50nm.

3. The tungsten oxide composite photoanode material according to claim 1, characterized in that: The mass of WO3 nanosheets on each square centimeter of substrate is 2-8 mg, the mass of Pt nanocrystals is 0.12-7.5% of the mass of WO3 nanosheets; the mass of Fe elements is 0.5%-0.7% of the mass of WO3 nanosheets; and the mass of Ni elements is 0.5%-0.7% of the mass of WO3 nanosheets.

4. The method for preparing the tungsten oxide composite photoanode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1. Place the substrate in a WO3 nanosheet precursor solution for hydrothermal growth at a hydrothermal temperature of 140-200°C for 3-8 hours, then wash and dry the sample and calcine it at 400-600°C for 1-3 hours to obtain a substrate for vertically growing WO3 nanosheets; S2, placing a uniformly dispersed Pt precursor solution on the substrate of the vertically grown WO3 nanosheets prepared in step S1, so that the surface of the WO3 nanosheets is loaded with Pt nanocrystals, and then drying at 50-70° C. to obtain a Pt / WO3 composite material; S3. A uniformly dispersed Fe and Ni element precursor solution is placed on the Pt / WO3 composite material prepared in step S2 to load Fe and Ni elements on the surface of the Pt / WO3 composite material, and then dried at 30-80°C to obtain the tungsten oxide composite photoanode material Pt / FeNi / WO3.

5. The preparation method according to claim 4, characterized in that: Before the hydrothermal process is carried out, the substrate in step S1 needs to be ultrasonically cleaned in acetone, ethanol and deionized water for 10-50 minutes respectively.

6. The preparation method according to claim 4, characterized in that: The WO3 nanosheet precursor solution in step S1 is prepared according to the following steps: (1) deionized water, concentrated hydrochloric acid and ammonium tungstate are stirred in a volume ratio of 20:1:1 to be fully mixed to obtain a WO3 nanosheet precursor a solution, wherein the concentrated hydrochloric acid is a 20-38% by mass aqueous solution of hydrogen chloride; (2) adding 30% aqueous hydrogen peroxide solution to the WO3 nanosheet precursor a solution, stirring thoroughly to mix evenly, to obtain a WO3 nanosheet precursor b solution, wherein the volume ratio of the aqueous hydrogen peroxide solution to the deionized water in step (1) is (0.8-1):45, preferably (0.85-0.9):45; (3) adding ammonium oxalate to the WO3 nanosheet precursor solution b, stirring thoroughly to mix evenly, to obtain the WO3 nanosheet precursor solution, wherein the volume ratio of ammonium oxalate to the deionized water in step (1) is (1-2):100, preferably (1-1.5):

100.

7. The preparation method according to claim 4, characterized in that: The uniform dispersion of the Pt precursor solution in step S2 is carried out according to the following steps: (1) mixing anhydrous methanol and a hexachloroplatinic acid aqueous solution uniformly to obtain a Pt precursor solution, wherein the volume ratio of anhydrous methanol to the hexachloroplatinic acid aqueous solution is (600-800):(1-10), and the concentration of platinum chloride in the hexachloroplatinic acid solution is 1-50 mg / ml; (2) The Pt precursor solution obtained in step (1) is placed under a xenon lamp and illuminated for 1-3 hours at an intensity of one sun.

8. The preparation method according to claim 4, characterized in that: The uniform dispersion of the Fe and Ni element precursor solutions in step S3 is carried out according to the following steps: (1) mixing anhydrous methanol, ferric chloride and nickel chloride uniformly to obtain Fe and Ni element precursor solutions, wherein the volume ratio of anhydrous methanol, ferric chloride and nickel chloride is (600-800):(1-5):(1-10); (2) The Fe and Ni element precursor solutions obtained in step (1) are placed under a xenon lamp and illuminated for 1-2 hours at an intensity of one sun.

9. The preparation method according to claim 4, characterized in that: The substrate needs to be cleaned before the drying steps in steps S2 and S3.

10. Use of the tungsten oxide composite photoanode material according to any one of claims 1 to 3 or the tungsten oxide composite photoanode material obtained by the preparation method according to any one of claims 4 to 9 in photoelectrocatalytic preparation of hydrogen peroxide.